Amount and quality of sleep: exploring the role of stress and work experience in a sample of obstetrician-gynecologists. (3rd July 2018) - Taouk, Laura; Farrow, Victoria A.; Schulkin, Jay
Abstract: Introduction: Sufficient sleep is necessary for optimal performance and the delivery of safe and effective health care. To establish an empirical understanding of physician fatigue, the present study investigated the factors that contributed to the amount and the quality of sleep among obstetricians and gynecologists (ob-gyns). Methods: A survey of personal and work experiences was sent to 495 eligible physicians belonging to the American College of Obstetricians and Gynecologists (ACOG). Data were obtained from 287 ob-gyns for a response rate of 58.0%. Associations between sleep-related items and measures of stress and work-related factors were explored. Results: Ob-gyns in our sample reported sleeping an average of 6.5 hours a night with 29.2% indicating that they received very or fairly bad quality of sleep. Average amount and quality of sleep were found to be independently related to the hours worked weekly, colleague support for a work-home balance, practice setting, perceived work-control, physician-specific stressors and perceived stress. In summary models, hours worked and perceived stress scores consistently emerged as predictors of amount of sleep. Conclusions: Overall, findings explained a small portion of the variance in sleep. Considering the multitude of factors that contribute to sleep, subtle associations warrant further investigation.